Composite film with bifunctional component structure layer and preparation method and application thereof
By introducing titanium and silver into the MoS2 film to form a bimetal composite layer, the problem of oxidation of traditional MoS2 films in high humidity and heat and high salt spray environments is solved, and higher oxidation resistance and mechanical strength are achieved, meeting the lubrication stability and long-life service requirements of aerospace machinery.
Patent Information
- Application Number
- CN202411897708.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional MoS2 films are prone to oxidation in high humidity and heat and high salt spray environments, resulting in a degradation of lubricating performance and it is difficult to meet the long-term and reliable service requirements of mechanical motion devices such as spacecraft and satellites in complex environments.
The titanium transition layer, titanium/silver/molybdenum disulfide gradient transition layer and dual-function component structural layer are deposited on the substrate surface in sequence to form a molybdenum disulfide/titanium-silver bimetallic composite layer. The multiphase protective layer is formed through the synergistic effect of titanium and silver, thereby improving the oxidation resistance and mechanical strength of the film.
It achieves excellent friction and wear performance in atmospheric, high humidity and high salt spray environments, significantly improves the corrosion resistance and environmental adaptability of the film, and meets the lubrication stability and long-life service requirements of aerospace machinery in harsh environments.
Smart Images

Figure CN119710588A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface protection, and in particular relates to a composite film with a dual-functional component structural layer and a preparation method and application thereof. Background Art
[0002] Molybdenum disulfide (MoS 2 ) Due to its unique layered structure, the molecular layers are weakly bonded by van der Waals and the shear stress between the layers is low, so it has very excellent vacuum lubrication performance and is widely used in the field of space lubrication. However, traditional MoS 2 The performance of the film in high humidity and high salt spray environment is not satisfactory. 2 The film is prone to oxidation, which leads to a significant decrease in its lubrication performance or even early failure. Moisture and high temperature accelerate the oxidation process of the film and reduce the MoS 2 With the commissioning and use of the Wenchang launch site, aerospace mechanical motion devices such as spacecraft and satellites will inevitably experience high humidity and heat environments during their entire service life, including transportation, storage, testing, simulated flight, and work. This has a great impact on the lubrication effect and mechanical strength of MoS 2 At the same time, in a high salt spray environment, MoS 2 Thin films also face severe challenges. Chloride ions in salt spray have a strong corrosive effect on thin films, which can easily destroy the structure of the thin films and cause the formation of oxides and other corrosion products on the surface, thus greatly reducing the lubrication performance and durability of the thin films. In marine engineering, coastal areas and other salt spray environments, MoS 2 The application of thin films is severely limited. Domestic and foreign researchers have used different technical means and methods to improve MoS 2 Environmental adaptability of the film, including the use of different preparation processes to regulate MoS 2 However, it is difficult for existing modification technologies to simultaneously improve the MoS 2 The film's oxidation resistance and mechanical strength are improved. Therefore, the development of new MoS 2The nano-solid lubricating film is based on nano-solid lubricating film to achieve the coordination and unification of durability and lubrication performance of the film in complex environments, which has important application value and practical significance for the long-term reliable service of spacecraft, satellites and other mechanical motion devices in harsh environments. The patent with publication number CN115341177A discloses a multilayer composite film with a sandwich structure layer and its preparation method and application, wherein a titanium transition layer, a titanium / molybdenum disulfide / ceramic / soft metal gradient transition layer and a sandwich structure layer are sequentially deposited on the surface of the substrate by magnetron sputtering technology to obtain a multilayer composite film with a sandwich structure layer. The film improves the toughness of the film and the bonding strength of the molybdenum disulfide / ceramic interface by introducing soft metal into the molybdenum disulfide / ceramic layer. On the other hand, it can promote the adhesion of the friction transfer film to the surface of the grinding ball, form a uniform and dense friction transfer film, and reduce friction and wear. However, since Ag exists in the form of particles, the bonding strength of the film may be insufficient due to the size and distribution of nanoparticles. Summary of the invention
[0003] The main purpose of the present invention is to provide a composite film with a dual-functional component structural layer and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0005] The embodiment of the present invention provides a composite film having a dual-functional component structure layer, which comprises: a titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer sequentially formed on the surface of a substrate;
[0006] Among them, the dual-functional component structural layer includes a molybdenum disulfide / titanium-silver bimetallic composite layer, which is formed by alternatingly stacking molybdenum disulfide layers and titanium-silver bimetallic layers, and titanium and silver in the titanium-silver bimetallic layer exist in the form of amorphous and / or nanocrystalline.
[0007] The embodiment of the present invention further provides a method for preparing the aforementioned composite film having a dual-functional component structure layer, which comprises:
[0008] By adopting unbalanced magnetron sputtering technology, a titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer are sequentially deposited on the substrate surface, thereby obtaining a composite film with a dual-functional component structure layer.
[0009] The embodiment of the present invention also provides the use of the aforementioned composite film having a dual-functional component structural layer in the surface protection of key motion devices of aerospace machinery.
[0010] Compared with the prior art, the present invention has the following beneficial effects:
[0011] (1) The composite film with a dual-functional component structure layer provided by the present invention has strong corrosion resistance and excellent environmental adaptability;
[0012] (2) The composite film with a dual-functional component structural layer in the present invention has good friction and wear properties in the atmosphere, high humidity and heat, and high salt spray environments, and exhibits excellent environmental adaptability, humidity and heat resistance, and salt spray resistance, and can meet the lubrication stability and high reliability service requirements of aerospace vehicles under harsh and complex and changeable working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 XRD diagrams of the composite film with a dual-functional component structure layer prepared in Example 1 of the present invention, the pure molybdenum disulfide film prepared in Comparative Example 1, and the molybdenum disulfide / silver composite film prepared in Comparative Example 2;
[0015] Figure 2a is a cross-sectional SEM image of the composite film having a dual-functional component structural layer prepared in Example 1 of the present invention;
[0016] Figure 2b is a cross-sectional SEM image of the pure molybdenum disulfide film prepared in Comparative Example 1 of the present invention;
[0017] Figure 2c is a cross-sectional SEM image of the molybdenum disulfide / silver composite film prepared in Comparative Example 2 of the present invention;
[0018] Figure 3a This is a surface optical morphology image of the composite film with a dual-functional component structural layer obtained in Example 1 of the present invention after being subjected to 7 days of salt spray corrosion;
[0019] Figure 3b This is a surface optical morphology image of the composite film with a dual-functional component structural layer obtained in Example 1 of the present invention after being subjected to 14 days of salt spray corrosion;
[0020] Figure 4 This is a surface optical morphology image of the pure molybdenum disulfide film prepared in Comparative Example 1 of the present invention after being subjected to 7 days of salt spray corrosion;
[0021] Figure 5a This is a surface optical morphology image of the molybdenum disulfide / silver multilayer film obtained in Comparative Example 2 of the present invention after being subjected to 7 days of salt spray corrosion;
[0022] Figure 5b This is a surface optical morphology image of the molybdenum disulfide / silver multilayer film prepared in Comparative Example 2 of the present invention after being subjected to 14 days of salt spray corrosion;
[0023] Figure 6a This is a surface optical morphology image of the molybdenum disulfide / titanium multilayer film prepared in Comparative Example 4 of the present invention after being subjected to 7 days of salt spray corrosion;
[0024] Figure 6b This is a surface optical morphology image of the molybdenum disulfide / titanium multilayer film prepared in Comparative Example 4 of the present invention after being subjected to 14 days of salt spray corrosion;
[0025] Figure 7 It is a friction coefficient curve diagram of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days;
[0026] Figure 8a This is a graph of average friction coefficient of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days;
[0027] Figure 8b This is a wear rate diagram of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days. DETAILED DESCRIPTION
[0028] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Specifically, as one aspect of the technical solution of the present invention, a composite film having a dual-functional component structure layer includes: a titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer sequentially formed on the surface of a substrate;
[0030] Among them, the dual-functional component structural layer includes a molybdenum disulfide / titanium-silver bimetallic composite layer, which is formed by alternatingly stacking molybdenum disulfide layers and titanium-silver bimetallic layers, and titanium and silver in the titanium-silver bimetallic layer exist in the form of amorphous and / or nanocrystalline.
[0031] The present invention provides a composite film with a dual-functional component structural layer, wherein the titanium-silver bimetallic composite layer significantly improves the density of the film through the effective combination of titanium and silver and the synergistic effect of the two, and effectively hinders the penetration of corrosive media; firstly, titanium has a high oxygen affinity, and in a high humidity and heat or salt spray environment, titanium will be preferentially oxidized to form a dense oxide layer, which can hinder the further penetration of the corrosive medium; secondly, silver itself has a low chemical activity and is not easy to corrode. Its presence can cause a "blocking effect" at the passivation film formed by titanium, fill its microscopic defects, and reduce the porosity of the passivation film; at the same time, the rapid passivation of titanium is combined with the "self-repairing" effect of silver to generate a multiphase protective layer, which has high density at the macro level and dynamic repair ability at the micro level, and can effectively inhibit the penetration and diffusion of corrosive media, thereby achieving excellent corrosion resistance. In addition, the synergistic presence of titanium and silver increases the interface strength and thermal stability of the film. In a high humidity and heat environment, the interface diffusion is more controlled, thereby reducing the interface failure caused by thermal expansion or ambient temperature difference.
[0032] In some preferred embodiments, the thickness modulation ratio of the molybdenum disulfide layer to the titanium-silver bimetallic layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 3 to 5:1.
[0033] In some preferred embodiments, the thickness of the molybdenum disulfide layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 10 to 30 nm.
[0034] In some preferred embodiments, the thickness of the titanium-silver bimetallic layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 2 to 10 nm.
[0035] In some preferred embodiments, the thickness of the titanium transition layer is 200-400 nm.
[0036] In some preferred embodiments, the thickness of the titanium / silver / molybdenum disulfide gradient transition layer is 200-400 nm.
[0037] In some preferred embodiments, the thickness of the dual-functional component structure layer is 2.1-2.5 μm.
[0038] In some preferred embodiments, the composite film has a hardness greater than 3 GPa and a hardness / elasticity ratio greater than 0.05.
[0039] In some preferred embodiments, the friction coefficient of the composite film at room temperature is less than 0.11, and the wear rate is less than or equal to 6.45×10 -6 mm 3 / N·m.
[0040] In some preferred embodiments, the corrosion depth of the composite film after 7 days of salt spray is less than 200 nm.
[0041] In some preferred embodiments, after 7 days of salt spray, the friction coefficient of the composite film at normal atmospheric temperature is less than 0.14, and the wear rate is less than or equal to 6.51×10 -6 mm 3 / N·m.
[0042] In some preferred embodiments, after 14 days of salt spray, the friction coefficient of the composite film at normal atmospheric temperature is less than 0.15, and the wear rate is less than or equal to 7.20×10 -6 mm 3 / N·m.
[0043] In some preferred embodiments, the material of the substrate includes any one of single crystal silicon wafer, Ti6Al4V, and 316 stainless steel.
[0044] The composite film with a dual-functional component structural layer in the present invention has a high hardness / elasticity ratio (0.05), and the component molybdenum disulfide preferentially grows along the (002) crystal plane parallel to the matrix, which greatly improves the environmental adaptability of molybdenum disulfide and exhibits excellent friction and wear properties in the atmosphere, high humidity, and high salt fog environment. After 14 days of salt spray test, the surface morphology of the film has no obvious change, the friction performance remains stable, and the wear rate is still less than or equal to 7.20×10 -6 mm 3 / N·m. The composite film with the dual-functional component structural layer can meet the requirements of lubrication stability and long service life of key moving parts of aerospace machinery in harsh environments.
[0045] The titanium in the present invention can significantly improve the hardness and load-bearing capacity of the film due to its high wear resistance and environmental stability; silver can improve the toughness of the film and increase the bonding strength of the nano-interface of the film; on the other hand, the introduction of the silver-titanium bimetallic layer helps to induce the MoS 2 The preferred growth along the (002) crystal plane parallel to the substrate eventually forms a nanocomposite multilayer structure with a dual-functional component structure layer of molybdenum disulfide / titanium-silver alternating growth. This novel dual-functional component structure layer can not only improve the corrosion resistance of the film, but also make full use of the advantages of each material; the present invention constructs a composite film with a dual-functional component structure layer, which will overcome the traditional MoS 2 The problem of early failure of films in high humidity, heat and salt spray environment.
[0046] The composite film with a dual-functional component structural layer provided by the present invention has strong corrosion resistance and excellent environmental adaptability; first, in the molybdenum disulfide / titanium-silver bimetallic composite layer with a dual-functional component structural layer, the titanium-silver bimetallic composite layer significantly improves the density of the film through the effective combination of titanium and silver and the synergistic effect of the two, and effectively hinders the penetration of corrosive media. Titanium has a high oxygen affinity. In a high humidity or salt spray environment, titanium will preferentially oxidize to form a dense oxide layer, which can hinder the further penetration of corrosive media; while silver itself has a low chemical activity and is not easy to corrode. Its presence can cause a "blocking effect" at the passivation film formed by titanium, fill its microscopic defects, and reduce the porosity of the passivation film. At the same time, the rapid passivation of titanium is combined with the "self-repairing" effect of silver to generate a multiphase protective layer. This protective layer has high density in the macroscopic sense and dynamic repair ability in the microscopic sense, which can effectively inhibit the penetration and diffusion of corrosive media, thereby achieving excellent corrosion resistance. In addition, the synergistic presence of titanium and silver increases the interface strength and thermal stability of the film. In high humidity and heat environments, interfacial diffusion is more controlled, thereby reducing interfacial failure caused by thermal expansion or ambient temperature differences.
[0047] The synergistic effect of the two functional factors effectively improves the shortcomings of the introduction of a single functional factor and significantly extends the service life of the film under high load and complex environment.
[0048] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned composite film having a dual-functional component structural layer, which comprises:
[0049] By adopting unbalanced magnetron sputtering technology, a titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer are sequentially deposited on the substrate surface, thereby obtaining a composite film with a dual-functional component structure layer.
[0050] In some preferred embodiments, when preparing the composite film having a dual-functional component structural layer, a six-target co-deposition technology is used for deposition, and two molybdenum disulfide targets, a titanium metal target, a silver metal target, and two molybdenum disulfide targets are arranged in a counterclockwise direction.
[0051] In some preferred embodiments, the rotation speed of the sample holder on which the substrate is placed is 0.5 to 2.0 rpm.
[0052] In some preferred embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using a titanium target as a cathode target material, using argon as a working gas, applying a target current to the titanium target, and applying a negative bias to the substrate, thereby depositing a titanium transition layer on the surface of the substrate; wherein, the target current is 3.0 to 5.0A, the substrate bias is -70 to -90V, the flow rate of the working gas is 12 to 16sccm, the pressure of the deposition chamber is 0.1 to 0.4Pa, the substrate temperature is 80 to 120°C, and the deposition time is 1200 to 1800s.
[0053] Furthermore, the working gas may be other inert gases other than argon.
[0054] In some preferred embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using titanium target, molybdenum disulfide target and silver target as cathode target materials, using argon as working gas, applying target current to the titanium target, molybdenum disulfide target and silver target, and applying negative bias to the substrate, so as to deposit a titanium / silver / molybdenum disulfide gradient transition layer on the surface of the titanium transition layer; wherein the target current applied to the titanium target is gradually reduced from 3.0 to 5.0 A to 0.4 A to 1.2 A (preferably 0.4 A, 0.6 A, 0.8 A, 1.0A, 1.2A, any one of them), the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6A, the target current applied to the silver target gradually increases from 0 to 0.1~0.4A (preferably any one of 0.1A, 0.2A, 0.3A, 0.4A), the substrate bias is -50~-70V, the flow rate of the working gas is 12~16sccm, the substrate temperature is 80~120℃, the pressure of the deposition chamber is 0.1~0.4Pa, and the deposition time is 1200~1800s.
[0055] Furthermore, the working gas may be other inert gases other than argon.
[0056] In some preferred embodiments, the preparation method specifically includes: using unbalanced magnetron sputtering technology, using molybdenum disulfide target, titanium target and silver target as cathode target materials, using argon as working gas, applying target current to the molybdenum disulfide target, titanium target and silver target, and applying a negative bias voltage to the substrate, thereby depositing a dual-functional component structure layer on the surface of the titanium / silver / molybdenum disulfide gradient transition layer; wherein the target current applied to the molybdenum disulfide target is 1.6A, and the target current applied to the titanium target is 0.4-1.2A (preferably any one of 0.4A, 0.6A, 0.8A, 1.0A, and 1.2A), the target current applied to the silver target is 0.1~0.4A (preferably any one of 0.1A, 0.2A, 0.3A, and 0.4A), the substrate bias is -50~-70V, the flow rate of the working gas is 12~16sccm, the substrate temperature is 80~120℃, the pressure of the deposition chamber is 0.1~0.4Pa, and the deposition time is 6000~8000s.
[0057] In some more specific embodiments, the method for preparing the composite film having a dual-functional component structural layer comprises the following steps:
[0058] (1) The titanium target current is 5.0 A, the substrate bias voltage is -70 to -90 V, the working gas is argon, the gas flow rate is 12 to 16 sccm, the deposition substrate temperature is 80 to 120° C., the pressure is 0.1 to 0.4 Pa, and the deposition time is 1200 to 1800 s to deposit a titanium transition layer on the substrate surface;
[0059] (2) the titanium target current is gradually reduced from 5.0A to 0.4-1.2A, the target current of the molybdenum disulfide target is gradually increased to 1.6A, the target current applied to the silver target is gradually increased to 0.1-0.4A, the substrate bias is -50--70V, the working gas flow rate is 12-16sccm, the substrate temperature is 80-120°C, the reaction chamber pressure is 0.1-0.4Pa, the deposition time is 1200-1800s, and then a titanium / silver / molybdenum disulfide gradient transition layer is deposited on the surface of the titanium transition layer, and the thickness of the transition layer is controlled between 200-400nm;
[0060] (3) The sputtering current of the molybdenum disulfide target is maintained at 1.6 A, and the sputtering current applied to the titanium target is increased to 0.4-1.2 A, and the sputtering current of the silver target is 0.1-0.4 A, until the deposition thickness of the dual-functional component structure layer reaches 2.1-2.5 μm.
[0061] In some preferred embodiments, the preparation method further comprises: evacuating the deposition chamber to a vacuum degree of 5.0×10 -3 Pa or less, and firstly subjecting the cleaned substrate to argon plasma etching treatment.
[0062] Furthermore, the plasma etching process includes: applying a substrate bias voltage of -400 to -500 V, and the etching time is 1800 s.
[0063] Furthermore, the preparation method further comprises: evacuating the reaction chamber to a predetermined vacuum degree (5.0×10 -3 Pa or less), the surface of the substrate is subjected to plasma etching to remove the oxide on the surface of the substrate; the specific etching method includes applying a bias voltage of -400 to -500 V to the substrate, etching the substrate at a temperature of 100 to 150° C., and etching time of 1200 to 1800 s.
[0064] Another aspect of the embodiments of the present invention further provides the use of the aforementioned composite film having a dual-functional component structural layer in the surface protection of key moving devices of aerospace machinery.
[0065] For example, the present invention provides the use of the aforementioned composite film having a dual-functional component structural layer in reducing surface friction or extending the life of key motion devices of aerospace machinery.
[0066] Furthermore, the material of the key motion device of the aerospace machinery includes any one of single crystal silicon wafer, Ti6Al4V, and 316 stainless steel, but is not limited thereto.
[0067] The inventors of this case also conducted the following performance tests on the composite film with a dual-functional component structure layer prepared above:
[0068] (1) The hardness and elastic modulus of the film were measured using an MTS NanoIndenter G200 nanoindentation system. The diamond indenter was inserted into a depth less than 1 / 10 of the film thickness to avoid the influence of the substrate. The average value was taken at six points. Test results: The hardness of the composite film with a dual-functional component structure layer in the present invention was greater than 3 GPa, and the hardness / elasticity ratio was greater than 0.05.
[0069] (2) Salt spray corrosion test: a salt spray test chamber (GM-90A) was used to evaluate the salt spray corrosion resistance of the film. The samples were pretreated before the test; the non-plated surface of the sample was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was carried out in accordance with the international standard AST-MB117. A 5.0wt% NaCl solution was sprayed in the chamber. The temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the film were placed in a salt spray chamber, and some samples were taken out after 7 days and 14 days of salt spray corrosion. Test results: The surface morphology of the composite film with a dual-functional component structure layer in the present invention did not change significantly after 7 days and 14 days of salt spray corrosion.
[0070] (3) Friction and wear test: CSM multifunctional friction testing machine was used to analyze the friction performance of the film under the conditions of atmospheric humidity of 75±5% RH and test temperature of 25±5°C. GCr15 steel balls were used as friction pairs, and a reciprocating sliding mode was adopted with a frequency of 5Hz, a sliding step length of 5mm, a running time of 30min, and a normal load of 5N. A contact step profiler was used to measure the cross-section of the wear area, and the wear volume of the film was calculated by multiplying it by the sliding step length. The wear rate was obtained by dividing the wear volume by the load and the total sliding distance. Test results: The optimal film of the present invention has a friction coefficient of 0.11 and a wear rate of 6.45×10 -6 mm 3 / N·m; after 7 days of salt spray, the friction coefficient is 0.14 and the wear rate is 6.51×10 - 6 mm 3 / N·m; after 14 days of salt spray, the friction coefficient is 0.15 and the wear rate is 7.20×10 -6 mm 3 / N·m.
[0071] In summary, through the above technical scheme, the composite film with a dual-functional component structural layer in the present invention has good mechanical properties, and can still maintain low friction and wear performance after 7 days and 14 days of salt spray test, showing excellent environmental adaptability, moisture and heat resistance, and salt spray resistance, and can meet the lubrication stability and long service life requirements of aerospace vehicles.
[0072] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0073] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0074] Example 1
[0075] In this embodiment, the substrate material is Ti6A14V, and / or 316 stainless steel, single crystal silicon wafer. The composite film having a dual-functional component structure layer is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0076] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0077] Targets are arranged in a counterclockwise direction: two MoS 2target (purity 99.9at.%), a Ti target (purity 99.99at.%), an Ag target (purity 99.9at.%), two MoS 2 Target (purity 99.9at.%).
[0078] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3 Pa, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 min, with the substrate temperature at 100-120 °C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 0.5 rpm to prepare the deposited MoS 2 / Ti-Ag dual-functional component structure layer structure nanocomposite multilayer film, the specific steps are as follows:
[0079] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0080] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 300 nm;
[0081] (3)Ti / Ag / MoS 2 Gradient transition layer: Ti target current gradually decreases to 0.8A, while MoS 2 The target current was set to 1.6A, the Ag target current was set to 0.2A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, the deposition time was 1800s, and Ti / Ag / MoS was deposited on the surface of the Ti transition layer. 2 The thickness of the gradient transition layer is about 300nm;
[0082] (4) MoS 2 / Ti-Ag bimetallic composite layer: Maintaining MoS 2 The target current was 1.6A, the Ti target current was 0.8A, the Ag target current was 0.2A, and the other deposition parameters remained unchanged. The deposition time was 7000s. 2 The thickness of the / Ti-Ag bimetallic composite layer is about 2.3μm; the total thickness of the composite film with a dual-functional component structural layer is controlled to be about 2.9μm.
[0083] The composite film with a dual-functional component structure layer obtained by the above deposition was tested as follows:
[0084] (1) Structural test:
[0085] The XRD results of the composite film are shown in Figure 1 As shown in the figure, the introduction of Ti-Ag dual-functional factors and the construction of double metal layers induce MoS 2 / Ti-Ag nanocomposite multilayer films with MoS 2 (002) orientation preferred growth; SEM of the cross section of the composite film is as follows Figure 2a As shown in the figure, the thickness of the Ti transition layer of the film is about 300nm, and the thickness of the Ti / Ag / MoS 2 The thickness of the nano-gradient transition layer is about 300nm; MoS 2 / Ti-Ag nanocomposite multilayer thickness is about 2.3μm; the total thickness of the multilayer composite film with dual functional component structural layers is about 2.9μm.
[0086] (2) Mechanical properties test:
[0087] The hardness and elastic modulus of the film were measured using an MTS NanoIndenter G200 nanoindenter system. The penetration depth of the diamond indenter was 1 / 10 of the film thickness. The average values of six measured points were taken, and the hardness was 3.4 GPa and the elastic modulus was 63.78 GPa.
[0088] (3) Salt spray corrosion test:
[0089] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the thin film were placed in a salt spray chamber, and some samples were taken out after 7 days and 14 days of salt spray corrosion. Test results: The surface morphology of the nanocomposite multilayer film with a dual-functional component structural layer in the present invention did not change significantly after 7 days and 14 days of salt spray corrosion.
[0090] Figure 3a This is a surface optical morphology image of the composite film with a dual-functional component structural layer obtained in Example 1 of the present invention after being subjected to 7 days of salt spray corrosion; Figure 3b This is a surface optical morphology image of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to 14 days of salt spray corrosion.
[0091] (4) Friction and wear performance test:
[0092] The tribological properties of the film were analyzed using a CSM multifunctional friction tester, with an atmospheric humidity of 75±5% RH and a test temperature of 25±5°C. A GCr15 steel ball was used as a friction pair, a reciprocating sliding mode was adopted, a frequency of 5Hz, a sliding step of 5mm, a running time of 30min, and a normal load of 5N. At the same time, the friction and wear properties of the film were analyzed before and after 7 days and 14 days of salt spray tests. The wear volume was measured using a contact step profiler, and the wear volume was divided by the load and the total sliding distance to obtain the wear rate. Figure 7 It is a friction coefficient curve diagram of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days; Figure 8a This is a graph of average friction coefficient of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days; Figure 8b This is a wear rate diagram of the composite film with a dual-functional component structural layer prepared in Example 1 of the present invention after being subjected to salt spray for 0 days, 7 days and 14 days.
[0093] Example 2
[0094] In this embodiment, the substrate material is Ti6A14V, and / or 316 stainless steel, single crystal silicon wafer. The composite film having a dual-functional component structure layer is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0095] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0096] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), an Ag target (purity 99.9at.%), two MoS 2 Target (purity 99.9at.%).
[0097] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3 Pa, the chamber was filled with high-purity argon gas, and then the target was cleaned by argon plasma sputtering for 30 minutes. The substrate temperature was 100N120℃. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 0.5 rpm to prepare the deposited MoS 2 / Ti-Ag dual-functional component structure layer structure nanocomposite multilayer film, the specific steps are as follows:
[0098] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0099] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 300 nm;
[0100] (3)Ti / Ag / MoS 2 Gradient transition layer: Ti target current gradually decreases to 0.8A, while MoS 2 The target current was set to 1.6A, the Ag target current was set to 0.1A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, the deposition time was 1800s, and Ti / Ag / MoS was deposited on the surface of the Ti transition layer. 2 The thickness of the gradient transition layer is about 300nm;
[0101] (4) MoS 2 / Ti-Ag bimetallic composite layer: Maintaining MoS 2 The target current was 1.6A, the Ti target current was 0.8A, the Ag target current was 0.1A, and the other deposition parameters remained unchanged. The deposition time was 7000s. 2 The thickness of the / Ti-Ag bimetallic composite layer is about 2.1 μm; the total thickness of the composite film with a dual-functional component structural layer is controlled to be about 2.7 μm.
[0102] The composite film with a dual-functional component structure layer obtained by the above deposition was tested as follows:
[0103] (1) Salt spray corrosion test:
[0104] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was carried out in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70N170 kPa. The samples deposited with the thin film were placed in a salt spray chamber, and some samples were taken out after 7 days and 14 days of salt spray corrosion. Test results: The surface morphology of the nanocomposite multilayer film with a dual-functional component structural layer in the present invention did not change significantly after 7 days of salt spray corrosion, and slight corrosion damage only appeared on the surface of the film after 14 days.
[0105] Example 3
[0106] In this embodiment, the substrate material is Ti6Al4V, and / or 316 stainless steel, single crystal silicon wafer. The composite film having a dual-functional component structure layer is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0107] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0108] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), an Ag target (purity 99.9at.%), two MoS 2 Target (purity 99.9at.%).
[0109] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3 Pa, the chamber was filled with high-purity argon gas, and then the target was cleaned by argon plasma sputtering for 30 minutes. The substrate temperature was 100N120℃. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 0.5 rpm to prepare the deposited MoS 2 / Ti-Ag dual-functional component structure layer structure nanocomposite multilayer film, the specific steps are as follows:
[0110] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of about 100°C to remove oxides on the substrate surface.
[0111] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 300 nm;
[0112] (3)Ti / Ag / MoS 2 Gradient transition layer: Ti target current gradually decreases to 0.8A, while MoS 2 The target current was set to 1.6A, the Ag target current was set to 0.1A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, the deposition time was 1800s, and Ti / Ag / MoS was deposited on the surface of the Ti transition layer. 2 The thickness of the gradient transition layer is about 300nm;
[0113] (4) MoS 2 / Ti-Ag bimetallic composite layer: Maintaining MoS 2 The target current was 1.6A, the Ti target current was 0.8A, the Ag target current was 0.3A, and the other deposition parameters remained unchanged. The deposition time was 7000s. 2 The thickness of the / Ti-Ag bimetallic composite layer is about 2.3μm; the total thickness of the composite film with a dual-functional component structural layer is controlled to be about 2.9μm.
[0114] The composite film with a dual-functional component structure layer obtained by the above deposition was tested as follows:
[0115] (1) Salt spray corrosion test:
[0116] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB 117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the thin film were placed in a salt spray chamber, and some samples were taken out after 7 days and 14 days of salt spray corrosion, respectively. Test results: The surface morphology of the nanocomposite multilayer film with a dual-functional component structural layer in the present invention did not change significantly after 7 days of salt spray corrosion, and slight corrosion damage only appeared on the surface of the film after 14 days.
[0117] Comparative Example 1
[0118] In this comparative example, the substrate material is Ti6Al4V, and / or 316 stainless steel, single crystal silicon wafer. The composite film is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0119] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0120] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), and three MoS 2 Target (purity 99.9at.%).
[0121] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3Pa, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes, and the substrate temperature was 100-120°C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 2 rpm to prepare the deposited pure MoS 2 Film, the specific steps are as follows:
[0122] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0123] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 200 nm;
[0124] (3)Ti / MoS 2 Gradient transition layer: Ti target current gradually decreases to 0.8A, while MoS 2 The target current was 1.6A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, and the deposition time was 1800s. Ti / MoS was deposited on the surface of the Ti transition layer. 2 The thickness of the gradient transition layer is about 300nm;
[0125] (4) Pure MoS 2 Thin film: Keep MoS 2 The target current is 1.6A, the deposition time is 7000s, and the pure MoS 2 The thickness is about 2.4 μm; the total thickness of the controlled nanocomposite multilayer film is about 2.9 μm.
[0126] The composite film obtained by the above deposition was tested as follows:
[0127] (1) Structural test:
[0128] The pure MoS 2 The XRD results of the film are shown in Figure 1 As shown, pure MoS 2 Thin film MoS 2 The (002) crystal plane orientation growth is not obvious; the SEM results of the film cross section are shown in Figure 3. The thickness of the Ti transition layer of the film is about 200nm. 2 The thickness of the gradient transition layer is about 300nm; pure MoS 2 The total thickness of the film is about 2.9 μm.
[0129] (2) Salt spray corrosion test:
[0130] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB 117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the thin film were placed in a salt spray chamber, and some samples were taken out after 7 days of salt spray corrosion. Test results: The surface morphology of the composite multilayer film in this comparative example showed obvious peeling after 7 days of salt spray corrosion, and the film had failed. Figure 4 This is a surface optical morphology image of the pure molybdenum disulfide film prepared in Comparative Example 1 of the present invention after being subjected to 7 days of salt spray corrosion.
[0131] (3) Friction and wear performance test:
[0132] The tribological properties of the film were analyzed using a CSM multifunctional friction tester, with an atmospheric humidity of 75±5% RH and a test temperature of 25±5°C. A GCr15 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5Hz, a sliding step of 5mm, a running time of 30min, and a normal load of 5N. At the same time, the friction and wear properties of the film were analyzed before and after 7 days and 14 days of salt spray tests. The wear volume was measured using a contact step profiler, and the wear volume was divided by the load and the total sliding distance to obtain the wear rate. The pure MoS in this comparative example 2 After 7 days of salt spray corrosion, the film's surface morphology showed obvious peeling, and the film had failed, so there was no need to test the friction coefficient and wear rate.
[0133] Comparative Example 2
[0134] In this comparative example, the substrate material is Ti6A14V, and / or 316 stainless steel, single crystal silicon wafer. The composite film is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0135] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0136] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), two MoS 2 target (purity 99.9at.%), an Ag target (purity 99.99at.%).
[0137] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 3×10 -3 Pa, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 min, with the substrate temperature at 100-120 °C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 0.5 rpm to prepare the deposited MoS 2 / Ag multilayer film, the specific steps are as follows:
[0138] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0139] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 100 nm;
[0140] (3)Ti / MoS 2 / Ag gradient transition layer: Ti target current gradually decreases to 0.8A, while gradually increasing MoS 2 The target current was set to 1.6A, the Ag target current was set to 0.2A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, the deposition time was 1800s, and Ti / MoS was deposited on the surface of the Ti transition layer. 2 / Ag gradient transition layer thickness is about 300nm;
[0141] (4) MoS 2 / Ag multilayer: Maintaining MoS 2 The target current was 1.6A, the Ag target current was 0.2A, the other deposition parameters remained unchanged, and the deposition time was 8000s. 2 / Ag multilayer film thickness is about 2.4μm; control MoS 2 The total thickness of the / Ag multilayer film is about 2.8μm.
[0142] The MoS obtained by the above deposition 2 / Ag multilayer films were tested as follows:
[0143] (1) Structural test:
[0144] The film XRD results are as follows Figure 1 As shown, MoS 2 MoS / Ag multilayer films 2Random orientation growth, Ag preferentially grows along the (111) orientation; the SEM results of the film cross section are as follows Figure 2c As shown in the figure, the thickness of the Ti transition layer to which the film belongs is about 100nm. 2 / Ag gradient transition layer thickness is about 300nm; MoS 2 / Ag multilayer thickness is about 2.4μm; MoS 2 The total thickness of the / Ag multilayer film is about 2.8μm.
[0145] (2) Salt spray corrosion test:
[0146] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the membrane-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB 117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the film were placed in a salt spray chamber, and some samples were taken out after 7 and 14 days of salt spray corrosion. Test results: The surface morphology of the nanocomposite multilayer film with a dual-functional component structural layer in the present invention has shown obvious corrosion damage after 7 days of salt spray corrosion, and serious corrosion damage has appeared on the surface of the film after 14 days, and the film has failed. Figure 5a The MoS prepared in Comparative Example 2 of the present invention 2 Surface optical morphology of Ag / Ag multilayer film after 7 days of salt spray corrosion; Figure 5b The MoS prepared in Comparative Example 2 of the present invention 2 Surface optical morphology of the MoS / Ag multilayer film after 14 days of salt spray corrosion. 2 After 7 days of salt spray corrosion, the surface morphology of the Ag / Ag multilayer film showed obvious corrosion, so there was no need to test the friction coefficient and wear rate.
[0147] Comparative Example 3
[0148] The method is the same as in Example 1, except that: MoS 2 / Ti-Ag bimetallic composite layer.
[0149] In this comparative example, the substrate material is Ti6Al4V, and / or 316 stainless steel, single crystal silicon wafer. The composite film is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0150] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0151] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), an Ag target (purity 99.9at.%), two MoS 2 Target (purity 99.9at.%).
[0152] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3 Pa, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes, and the substrate temperature was 100-120°C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 2 rpm to prepare the deposited pure MoS 2 Film, the specific steps are as follows:
[0153] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0154] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 300 nm;
[0155] (3)Ti / MoS 2 / Ag gradient transition layer: Ti target current gradually decreases to 0.8A, while gradually increasing MoS 2 The target current was set to 1.6A, the Ag target current was set to 0.2A, the working gas was argon, the gas flow rate was 16sccm, the substrate bias was -50V, the substrate deposition temperature was about 100℃, the pressure was about 0.3Pa, the deposition time was 1800s, and Ti / MoS was deposited on the surface of the Ti transition layer. 2 / Ag gradient transition layer thickness is about 300nm;
[0156] The composite film obtained by the above deposition was tested as follows:
[0157] (1) Salt spray corrosion test:
[0158] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the film-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the thin film were placed in a salt spray chamber, and some samples were taken out after 7 days of salt spray corrosion. Test results: The lack of MoS in the present invention 2 After 7 days of salt spray corrosion, the surface morphology of the / Ti-Ag bimetallic composite film showed obvious peeling, and the film had failed.
[0159] Comparative Example 4
[0160] In this comparative example, the substrate material is Ti6Al4V, and / or 316 stainless steel, single crystal silicon wafer. The composite film is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:
[0161] The mechanically polished substrate material was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; subsequently, the substrate material was placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use.
[0162] Targets are arranged in a counterclockwise direction: two MoS 2 target (purity 99.9at.%), a Ti target (purity 99.99at.%), and three MoS 2 Target (purity 99.9at.%).
[0163] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 5×10 -3 Pa, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes, and the substrate temperature was 100-120°C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 2 rpm to prepare the deposited pure MoS 2 Film, the specific steps are as follows:
[0164] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.
[0165] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 0.3 Pa, deposition time is 1200 s, and a Ti transition layer is deposited on the substrate surface with a thickness of about 300 nm;
[0166] (3) MoS 2 / Ti multilayer: Maintaining MoS 2 The target current was 1.6 A, the Ti target current was reduced to 0.8 A, the other deposition parameters remained unchanged, and the deposition time was 7000 s.
[0167] The composite film obtained by the above deposition was tested as follows:
[0168] (1) Salt spray corrosion test:
[0169] The samples were pretreated before the test, and the non-plated surface of the samples was encapsulated with waterproof glue to prevent the corrosive medium from diffusing through the film-substrate interface and corroding the substrate material. The salt spray test was conducted in a salt spray test chamber (GM-90A) in accordance with the international standard AST-MB117 for neutral salt spray corrosion testing. A 5.0wt% NaCl solution was sprayed in the chamber, and the temperature in the chamber was kept constant at 35±5°C, and the air pressure in the chamber was maintained at 70-170kPa. The samples deposited with the thin film were placed in the salt spray chamber, and some samples were taken out after 7 and 14 days of salt spray corrosion. Test results: The MoS 2 After 7 days of salt spray corrosion, the surface morphology of the Ti / Ti multilayer film showed obvious corrosion damage, and after 14 days, the surface of the film had suffered severe corrosion damage, and the film failed. Figure 6a The MoS obtained in Comparative Example 4 of the present invention is 2 Surface optical morphology of the / Ti multilayer film after 7 days of salt spray corrosion. Figure 6b The MoS obtained in Comparative Example 4 of the present invention is 2 Surface optical morphology of the MoS / Ti multilayer film after 14 days of salt spray corrosion. 2 After 7 days of salt spray corrosion, the surface morphology of the Ti / Ti multilayer film showed obvious corrosion, so there was no need to test the friction coefficient and wear rate.
[0170] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0171] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A composite film having a dual-functional component structural layer, characterized in that: include: A titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer are sequentially formed on the surface of the substrate; Among them, the dual-functional component structural layer includes a molybdenum disulfide / titanium-silver bimetallic composite layer, which is formed by alternatingly stacking molybdenum disulfide layers and titanium-silver bimetallic layers, and titanium and silver in the titanium-silver bimetallic layer exist in the form of amorphous and / or nanocrystalline.
2. The composite film according to claim 1, characterized in that: The thickness modulation ratio of the molybdenum disulfide layer to the titanium-silver bimetallic layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 3 to 5:1; And / or, the thickness of the molybdenum disulfide layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 10 to 30 nm; and / or, the thickness of the titanium-silver bimetallic layer in the molybdenum disulfide / titanium-silver bimetallic composite layer is 2 to 10 nm; And / or, the thickness of the titanium transition layer is 200-400 nm; and / or, the thickness of the titanium / silver / molybdenum disulfide gradient transition layer is 200-400 nm; and / or, the thickness of the dual-functional component structure layer is 2.1-2.5 μm.
3. The composite film according to claim 1, characterized in that: The hardness of the composite film is greater than 3 GPa, and the hardness / elasticity ratio is greater than 0.05; And / or, the friction coefficient of the composite film at normal atmospheric temperature is less than 0.11, and the wear rate is less than or equal to 6.45×10 - 6 mm 3 / N·m; and / or, the corrosion depth of the composite film after 7 days of salt spray is less than 200 nm; And / or, after the composite film is exposed to salt spray for 7 days, the friction coefficient is less than 0.14 at normal atmospheric temperature, and the wear rate is less than or equal to 6.51×10 -6 mm 3 / N·m; And / or, after 14 days of salt spray, the friction coefficient of the composite film at normal atmospheric temperature is less than 0.15, and the wear rate is less than or equal to 7.20×10 -6 mm 3 / N·m.
4. The composite film according to claim 1, characterized in that: The material of the substrate includes any one of single crystal silicon wafer, Ti6Al4V, and 316 stainless steel.
5. The method for preparing a composite film having a dual-functional component structural layer according to any one of claims 1 to 4, characterized in that: include: By adopting unbalanced magnetron sputtering technology, a titanium transition layer, a titanium / silver / molybdenum disulfide gradient transition layer and a dual-functional component structure layer are sequentially deposited on the substrate surface, thereby obtaining a composite film with a dual-functional component structure layer.
6. The preparation method according to claim 5, characterized in that: When preparing the composite film having the dual-functional component structural layer, a six-target co-deposition technique is used for deposition, and two molybdenum disulfide targets, a titanium metal target, a silver metal target, and two molybdenum disulfide targets are arranged in a counterclockwise direction in sequence; And / or, the rotation speed of the sample holder on which the substrate is placed is 0.5 to 2.0 rpm.
7. The preparation method according to claim 5, characterized in that: Specifically include: An unbalanced magnetron sputtering technique is adopted, with a titanium target as a cathode target material, argon as a working gas, a target current applied to the titanium target, and a negative bias applied to the substrate, so as to deposit a titanium transition layer on the surface of the substrate; wherein, the target current is 3.0 to 5.0 A, the substrate bias is -70 to -90 V, the flow rate of the working gas is 12 to 16 sccm, the pressure of the deposition chamber is 0.1 to 0.4 Pa, the substrate temperature is 80 to 120°C, and the deposition time is 1200 to 1800 s.
8. The preparation method according to claim 5, characterized in that: Specifically include: An unbalanced magnetron sputtering technique is adopted, titanium target, molybdenum disulfide target and silver target are used as cathode target materials, argon gas is used as working gas, target current is applied to the titanium target, molybdenum disulfide target and silver target, and a negative bias voltage is applied to the substrate, so as to deposit a titanium / silver / molybdenum disulfide gradient transition layer on the surface of the titanium transition layer; wherein, the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0.4 A to 1.2 A, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6 A, the target current applied to the silver target gradually increases from 0 to 0.1 to 0.4 A, the substrate bias voltage is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120° C., the pressure of the deposition chamber is 0.1 to 0.4 Pa, and the deposition time is 1200 to 1800 s.
9. The preparation method according to claim 5, characterized in that: Specifically include: An unbalanced magnetron sputtering technique is adopted, a molybdenum disulfide target, a titanium target and a silver target are used as cathode target materials, argon is used as a working gas, a target current is applied to the molybdenum disulfide target, the titanium target and the silver target, and a negative bias is applied to the substrate, so as to deposit a dual-functional component structure layer on the surface of the titanium / silver / molybdenum disulfide gradient transition layer; wherein, the target current applied to the molybdenum disulfide target is 1.6A, the target current applied to the titanium target is 0.4-1.2A, the target current applied to the silver target is 0.1-0.4A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, the pressure of the deposition chamber is 0.1-0.4Pa, and the deposition time is 6000-8000s.
10. Use of the composite film having a dual-functional component structural layer as claimed in any one of claims 1 to 4 in surface protection of key moving devices of aerospace machinery.
Citation Information
Patent Citations
Multi-layer composite film with sandwich structure layer as well as preparation method and application of multi-layer composite film
CN115341177A